The Toxicity of Bullying by Teachers and Other School Staff. Issue 4 (1st December 2017) - Datta, Pooja; Cornell, Dewey; Huang, Francis
Abstract: Although the toxic effects of peer bullying among middle school students are widely recognized, bullying by teachers and other school staff has received little attention. This study compared the prevalence and school adjustment of students bullied by teachers/staff, students bullied by peers, and students who were not bullied. The sample consisted of 56, 508 students in Grades 7 and 8 who completed a statewide school climate survey. Students were classified into four groups: (a) not bullied (87.2%); (b) bullied only by peers (9.3%); (c) bullied only by teachers/staff (1.2%); and (d) bullied by peers and teachers/staff (1.5%). In comparison to students who reported no bullying, students bullied by teachers and other school staff were significantly more likely to report lower school engagement and self-reported grades and more negative perceptions of school climate. Students bullied only by peers reported more distress symptoms than those bullied by teachers and other school staff. These findings call for more attention to the problem of teacher and other school staff bullying.